Action Control and Mental Health in Islamic Teachings and the Academic Achievement of Entrance Exam Students: The Mediating Role of Self-esteem - Farrokhi, Farimah; Kiani, Qamar; Sobhi, Afsaneh (Advances in Nursing & Midwifery, 2023)
Abstract Introduction: The aim of the present study was to investigate the mediating role of self-confidence in the relationship between action control and mental health based on Islamic teachings and students’ academic progress. Methods: The current research was applied in terms of purpose and in terms of nature, method, and design of correlation and structural equations. The statistical population of the current study was all female students of the second secondary level in Zanjan city in the academic year 2022-2023, of whom 550 were selected by the random cluster method. In order to collect data, action-control questionnaires were used: this one was used by Diefendorf et al.’s. for mental health based on the Islamic teachings of Abol-Maali al-Husseini and Mousazadeh; Gilbert et al.’s self-confidence; and Pham and Taylor’s academic achievement questionnaire. In order to analyze the data, SPSS version 25 and SmartPLS version 3.3 and the structural equation method were used. Results: The direct effect of action control on academic achievement and self-confidence is significant (p< 0.05). The direct effect of mental health based on Islamic teachings on academic progress and self-confidence is significant (p < 0.05). The indirect effect of action control on academic achievement through self-confidence is not significant (p < 0.05). The indirect effect of mental health based on Islamic teachings through self-confidence on academic achievement is not significant (p < 0.05). The results of the goodness of fit indices of the model showed that the research model had a good goodness of fit (SRMR = 0.000, 1 = NFI, GOF = 0.38). Conclusions: Based on the findings of the present research, it is suggested that school counselors provide the means for students’ academic progress by strengthening their mental health based on Islamic teachings and their self-confidence.